Differences in drug use behaviors that impact overdose risk among individuals who do and do not use fentanyl test strips for drug checking - Alyssa Shell Tilhou; Jen Zaborek; Amelia Baltes; Elizabeth Salisbury-Afshar; Julia Malicki; Randall Brown (BMC, 2023)
Abstract Background Opioid-involved overdose continues to rise, largely explained by fentanyl adulteration of the illicit opioid supply. Fentanyl test strips are a novel drug checking tool that can be used by people who use drugs to detect the presence of fentanyl in drug products. However, it is unclear whether fentanyl test strip use can prompt behavior changes that impact risk of overdose. Methods In this mixed-methods study involving a structured survey (n = 341) of syringe service program clients in southern Wisconsin, we examined the association between fentanyl test strip use and overdose risk behaviors in scenarios where the presence of fentanyl is confirmed and unknown. Individual items were transformed into summary scales representing the performance of riskier and safer behaviors. Linear regression examined the association of behaviors with FTS use. Models are adjusted for study site, race/ethnicity, age, gender, drug of choice, indicator of polysubstance use, times used per day, and lifetime overdose count. Results In response to survey questions before prompting about fentanyl risk, people who used fentanyl test strips reported an increased number of safer (p = 0.001) as well as riskier behaviors (p = 0.018) relative to people who did not use fentanyl test strips. The same held true in situations when fentanyl adulteration was suspected, though fentanyl test strip use lost significance in the fully adjusted model examining safer behaviors (safer: p = 0.143; riskier: p = 0.004). Among people who use fentanyl test strips, in unadjusted models, a positive test result was associated with more safer behaviors and fewer riskier behaviors, but these associations became nonsignificant in fully adjusted models (safer: p = 0.998; riskier: p = 0.171). Loss of significance was largely due to the addition of either polysubstance use or age to the model. Conclusions Fentanyl test strip use is associated with behaviors that may impact overdose risk, including safer and riskier behaviors. Specifically, a positive test result may promote more risk reducing behaviors and fewer risk enhancing behaviors than a negative test result. Results suggest that while FTS may promote safer drug use behaviors, outreach and education should emphasize the need for multiple harm reduction techniques in all scenarios.